PENGELOLAAN PERIKANAN PELAGIS KECIL BERBASIS DAYA DUKUNG LINGKUNGAN PERAIRAN DI KEPULAUAN SANGIHE - Achmad Nasir Biasane; Akhmad Fauzi; Daniel R. Monintja; Dedi Soedharma (Graduate School Bogor Agricultural University (SPs IPB), 2012)
One of the potency for development of Sangihe Islands is sea and the availability of fish resources which is relatively high, both in terms of quantity and diversity. One of the fish types with high quantity in this area are pelagic fish group. This research aims to analyze the management of small pelagic fishing in order to maintain its sustainability. The research result indicate that the average sustainable production of the small pelagic for 20 years (1988-2007) observation was 3,128.45 tons/year. Depreciation value has reduced the rents value received by fishermen. With the method of the present value, the revenues from the market at discount rate of 15% should be Rp 274.97 billion. However, due to depreciation, the amount received just Rp 118.59 billion only. For the optimal and sustainable fisheries management, the effort level for small pelagic capture should be 5,342 trips/year at discount rate of 15%. To maintain the sustainability, the level should be lowered down around 46% from the present level in small pelagic management. Keywords : Sangihe archipelago, CYP, MAPLE, development of the small pelagic fishes